FOOD SAFETY MANAGEMENT LEADERSHIP STYLE: TRANSFORMATIONAL OR TRANSACTIONAL? - Agus Purwanto; Leo Hutagalung; Evy Yanthy (Universitas Muhammadiyah Kalimantan Timur, 2020)
The purpose of this study was to analyze the effect of transformational and transactional leadership style on the performance of the latest version of the FSSC 22000 (Food Safety System Certification) food safety management system, version 5 of 2019 in the food industry in Tangerang. The object of the research were employees in several food industries that worked in the Tangerang City area who had implemented FSSC 22000 version 5 2019; as many as 120 people, and data collection method was done by giving out electronic questionnaire to several employees randomly. The analysis tool in this study used SEM (Structural Equation Model) LISREL program version 8.70. The results showed that the transformational leadership style positively and significantly affected the performance of the FSSC 22000 implementation and the transactional leadership style also contributed positive effect on the performance of the FSSC 22000 food safety management system and it can be concluded that leadership was important for the implementation of the FSSC 22000 Food Safety Management System.